FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PRE HIPERTENSI PADA USIA 18-40 TAHUN DI DESA JATI KESUMA KECAMATAN NAMO RAMBE KABUPATEN DELI SERDANG TAHUN 2015 - sri dewi puspita; Rasmaliah .; Taufik Ashar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTPre hypertension was blood pressure with the systolic numbers between 120 to 139 mmHg or diastolic number was between 80 to 89 mmHg. Pre hypertension and hypertension were disease unit caused by any risk factors. The main purpose of this research was done to determine the factors associated with the incidence of pre-hypertension at age 18-40 years in village of Jati Kesuma, Namo Rambe district, Deli Serdang in 2015.This research was analytic study using cross sectional study. The number of sample was 115 person in age of 18-40 years old and without hypertension that took by consecutive sampling. The research instrument was questionnaire, digital tension meter, balance, measurer and direct observation. The univarian data was analyzed by descriptive study and bivarian data was analyzed by Chi square test with 95% CI.Based on data coleccting the proportion prevalence of pre hypertension was 53,9%. There was significanted correlation between gender (p = 0.001), employment (p = 0.042), genetic (p = 0.049), stress (p = 0.009), salt intake (p = 0.001), smoking (p =0.007) and consumption of alcohol (p = 0.030) with pre hypertension event.To the patient of pre hypertension was suggted to avoided the risk factors, especially stress, high salt intake, smoking and consumption of alcohol. And to the health center was expected to provided direction and health extension of pre hypertension / hypertension for the health center visitors about the importance of keeping blood pressure as early as possible and avoided the risk factors that may cause pre hypertension / hypertension event.Key Words: Salt Intake, Smoking, Pre Hypertension